2019
DOI: 10.1107/s2052252519008157
|View full text |Cite
|
Sign up to set email alerts
|

Ligand pathways in neuroglobin revealed by low-temperature photodissociation and docking experiments

Abstract: A combined biophysical approach was applied to map gas-docking sites within murine neuroglobin (Ngb), revealing snapshots of events that might govern activity and dynamics in this unique hexacoordinate globin, which is most likely to be involved in gas-sensing in the central nervous system and for which a precise mechanism of action remains to be elucidated. The application of UV–visible microspectroscopy in crystallo, solution X-ray absorption near-edge spectroscopy and X-ray diffraction experiments at 15–40 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 76 publications
1
11
0
Order By: Relevance
“…Initial CO positions in the active site of the wild type protein and the protein mutations were created manually in accordance with previous experimental and theoretical studies of NgbCO (see Figure 1). 30,34,109,114 As suggested in the literature, the dissociated CO preferentially adapts two different orientations, where either CO is located perpendicular to the plane defined by the distal histidine (form A) or parallel to that plane (form B). Furthermore, in each of the two docking forms A and B CO can be placed initially in two opposite orientations before the geometry optimization, one where the C atom is closer to the heme center (denoted in our study as 1) and one where the O atom is closer to the heme center (denoted as 2) which led to 36 protein systems denoted in this work as: F106A δ 1, F106A δ 2, F106A ϵ 1, F106A ϵ 2, F28L δ 1, F28L δ 2, F28L ϵ 1, F28L ϵ 2, F28W δ 1, F28W δ 2, F28W ϵ 1, F28W ϵ 2, H64A1, H64A2, H64Q1, H64Q2, H64V1, H64V2, H64 δ 1, H64 δ 2, H64 ϵ 1, H64 ϵ 2, H64 δϵ 1, H64 δϵ 2, K67A δ 1, K67A δ 2, K67A ϵ 1, K67A ϵ 2, K67R δ 1, K67R δ 2, K67R ϵ 1, K67R ϵ 2, K67T δ 1, K67T δ 2, K67T ϵ 1, and K67T ϵ2 , where 1 and 2 denote complexes obtained from different starting orientations.…”
Section: Methodsmentioning
confidence: 89%
See 1 more Smart Citation
“…Initial CO positions in the active site of the wild type protein and the protein mutations were created manually in accordance with previous experimental and theoretical studies of NgbCO (see Figure 1). 30,34,109,114 As suggested in the literature, the dissociated CO preferentially adapts two different orientations, where either CO is located perpendicular to the plane defined by the distal histidine (form A) or parallel to that plane (form B). Furthermore, in each of the two docking forms A and B CO can be placed initially in two opposite orientations before the geometry optimization, one where the C atom is closer to the heme center (denoted in our study as 1) and one where the O atom is closer to the heme center (denoted as 2) which led to 36 protein systems denoted in this work as: F106A δ 1, F106A δ 2, F106A ϵ 1, F106A ϵ 2, F28L δ 1, F28L δ 2, F28L ϵ 1, F28L ϵ 2, F28W δ 1, F28W δ 2, F28W ϵ 1, F28W ϵ 2, H64A1, H64A2, H64Q1, H64Q2, H64V1, H64V2, H64 δ 1, H64 δ 2, H64 ϵ 1, H64 ϵ 2, H64 δϵ 1, H64 δϵ 2, K67A δ 1, K67A δ 2, K67A ϵ 1, K67A ϵ 2, K67R δ 1, K67R δ 2, K67R ϵ 1, K67R ϵ 2, K67T δ 1, K67T δ 2, K67T ϵ 1, and K67T ϵ2 , where 1 and 2 denote complexes obtained from different starting orientations.…”
Section: Methodsmentioning
confidence: 89%
“…This triggers a larger conformational reorganization of the protein, as confirmed for the crystal structure of carbon monoxide bound murine Ngb. 34 Far-IR and THz domain spectroscopy, 35 resonance Raman, 26,36,37 and time-resolved resonance Raman, 38 complemented with computational investigations 39,40 have suggested that the biological function of Ngb and other globins is related in particular to the strength of the Fe-L bond, however these effects were not quantified.…”
Section: Introductionmentioning
confidence: 99%
“…A unique structural feature of murine Ngb is the heme sliding within the heme crevice upon ligand binding, resulting in an iron displacement of 2 A [18][19][20][21]. Recently, a spectroscopic and structural characterization of the CO complexes of the wild-type (WT) murine Ngb, the CD loop mutant 'Gly-loop [44][45][46][47] ' endowed with enhanced flexibility, the F106A mutant, and the double Gly-loop [44][45][46][47] /F106A mutant (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The possible involvement of nearby temporary docking sites is suggested by the presence of a process of small amplitude endowed with a lifetime of ∼7 μs that can be identified only in the CDless mutant ( Supporting Information Table S5 ) and that may arise from the migration of photodissociated CO molecules to kinetic traps, as observed for murine and icefish Ngbs at low temperature. 27 , 31 , 38 We used a simple model ( eq 1 ) to describe the geminate rebinding on the nanosecond time scale when His64 recombination is negligible, where we assume that the photodissociated ligand may either exit the protein matrix or rebind from the distal pocket …”
Section: Resultsmentioning
confidence: 99%